Keep an Eye on the Back: Spondyloarthritis in Patients With Acute Anterior Uveitis. Issue 2 (23rd December 2022) - Rademacher, Judith; Müllner, Hanna; Diekhoff, Torsten; Haibel, Hildrun; Igel, Sabrina; Pohlmann, Dominika; Proft, Fabian; Protopopov, Mikhail; Rios Rodriguez, Valeria; Torgutalp, Murat; Pleyer, Uwe; Poddubnyy, Denis
Abstract : Objectives: This study was undertaken to analyze the prevalence of spondyloarthritis (SpA) in patients with acute anterior uveitis (AAU), to identify parameters associated with the presence of SpA, and to evaluate the performance of referral algorithms for identifying patients with a high probability of having SpA. Methods: Prospectively recruited consecutive patients with noninfectious AAU underwent structured rheumatologic assessment including magnetic resonance imaging of the sacroiliac joints, allowing a definitive diagnosis/exclusion of concomitant SpA. Fisher's exact test and Mann‐Whitney U test were used to compare AAU patients with SpA and AAU patients without SpA. Furthermore, logistic regression analyses were performed. The predictive performance of SpA referral strategies was analyzed by calculating the sensitivity, specificity, positive predictive value, and positive and negative likelihood ratios. Results: Among the 189 AAU patients evaluated, 106 (56%) were diagnosed as having SpA. The majority of SpA patients (93%) had predominantly axial SpA and 7 patients had peripheral SpA. In 74 patients (70%), the SpA diagnosis was established for the first time. In multivariable logistic regression analysis, psoriasis (odds ratio [OR] 12.5 [95% confidence interval (95% CI) 1.3–120.2]), HLA–B27 positivity (OR 6.3 [95% CI 2.4–16.4]), elevated C‐reactive protein level (OR 4.8 [95% CI 1.9–12.4]), and male sex (OR 2.1 [95% CI 1.1–4.2]) were associated with the presence of SpA. None of the ophthalmologic parameters were found to be predictive of SpA. The Dublin Uveitis Evaluation Tool (DUET) showed higher specificity for SpA recognition than the Assessment of SpondyloArthritis international Society (ASAS) tool for the early referral of patients with a suspected diagnosis of axial SpA (specificity for SpA 42% versus 28%), whereas the sensitivity of the ASAS tool was slightly higher than the DUET tool (sensitivity for SpA 80% versus 78%). However, more than 20% of the AAU patients in this study who were diagnosed as having SpA would have been missed by both referral strategies. Conclusion: Our study revealed a high prevalence of SpA in AAU patients overall, as well as a high prevalence of previously undiagnosed SpA in AAU patients. Therefore, we propose rheumatologic evaluation for all AAU patients with musculoskeletal symptoms.